Educação à distância corporativa: da informação à experiência - Castro, Gisele Vieira de Oliveira (2012)
Corporate distance education has been growing considerable in the last years. This growth is due to, between many reasons, the low price compared with presential training, the possibility to reuse the same content for thousand people without additional expense, the decrease of time spent with training and information management. Within this context, we may ask: are numbers enough to ensure we are in the right way with regard to corporate distance education in the Digital Era? To answer this question, we took as basis Phenomenology, theory whereby perception is our first cognitive instance, our first contact with the external world. Thereafter, we interspersed the concept of perception, technique and digital technology, with support of the following authors: Maturana, Varela, Flusser, Pierre Lèvy, André Parente, Basbaum, Heidegger, and others. Then, we discussed, from Bondía s perspective, education as legitimization of practices and knowledge instituted by the technique, considered as reality and truth, and this discourse pervades the corporate distance education contents and enhances the model s digital though, of maximum efficiency and lower noise. Finally, we propose the resumption of experience as starting point in corporate distance education and some suggestions for how to do it in current context, considering experience as multiple, opened, and, therefore incalculable